A cross-sectional study to assess the quality of life among cancer patients in a tertiary care hospital in a metropolitan city - B., Abhinand Sai M.; G., Prahatheeswaran; Rao, D. H.; Gokhe, Seema S. Bansode (International Journal Of Community Medicine And Public Health, 2023)
Background: Cancer is a major cause of morbidity and mortality worldwide. Quality of life measures have now become a vital part of health outcome appraisal and an effective way of capturing the personal and social context of patients. The diagnosis of cancer brings many challenges, with a major concern being maintaining the highest quality of life possible during and after the experience. The objectives of the study were to assess the health-related quality of life among cancer patients and also to study the effects of type of cancer and treatment received after one month on their quality of life. Methods: It was a descriptive, cross sectional and hospital-based study. Total duration of study was 6 months (August 2019-February2020), conducted in Oncology department of a Tertiary care hospital. A total of 90 cancer patients were selected as study subjects and interviewed by a validated SF-36 questionnaire. Results: A total of 90 cancer patients were included in the study, of which 18 were males and 72 were females and majority were in the age range of 40-60 years. 75% of cancer patients were living a below average quality of life. The study population had different types of cancers. Among females 50% patients were suffering from CA Breast and remaining patients were suffering from different types of cancer. Conclusions: Most of the patients who came to the oncology department of tertiary care hospital during our period of study had low quality of life.